2022
DOI: 10.1186/s12877-021-02730-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between socio-ecological factors and leisure time physical activity (LTPA) among older adults in Sichuan, China: a structural equation modeling analysis

Abstract: Background Few studies examined socio-ecological factors and leisure time physical activities (LTPA) and rarely focused on self-regulation and social capital, which might play a significant role in impacting people’s physical activity behavior. This study aimed to examine the direct and indirect effects of individual level (perceived benefits, perceived barriers, and self-efficacy), interpersonal level (self-regulation), social level (social capital), and environmental level factors (perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Among them, walking speed is also often used as an overall measure of preparedness for safe community mobility [ 83 , 84 ], further supporting the positive relationships between the individual variables related to walking capacity and OW. Walking self-efficacy, which refers to older adults’ confidence in walking outdoors, should predict OW behaviour based on self-efficacy theory [ 85 ] and has been shown to be significantly related to physical activity in several studies [ 22 , 86 , 87 ]. Individuals with higher income have been shown to have higher levels of mobility [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, walking speed is also often used as an overall measure of preparedness for safe community mobility [ 83 , 84 ], further supporting the positive relationships between the individual variables related to walking capacity and OW. Walking self-efficacy, which refers to older adults’ confidence in walking outdoors, should predict OW behaviour based on self-efficacy theory [ 85 ] and has been shown to be significantly related to physical activity in several studies [ 22 , 86 , 87 ]. Individuals with higher income have been shown to have higher levels of mobility [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using SEM, the correlation among observed variables can be accounted for by assuming a latent construct to be an underlying factor [ 21 ]. One study in this area applied an SEM approach and found that leisure time physical activities were significantly associated with individual level variables (i.e., perceived exercise benefits and barriers, and exercise self-efficacy) while not significantly associated with environmental level variables [ 22 ]. Another study applied SEM and found that individual factors (i.e., self-efficacy, perceived pros and cons of physical activity, and social support) had direct influences on physical activity, while the environmental factors affected physical activity indirectly through individual and social factors [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…ADL or IADL each represents daily self-care activities to support fundamental functioning or independent living [ 24 ], with ADL or IADL impairment identified by a total Barthel Index score below 100 or Lawton IADL Scale score below 14, respectively [ 25 , 26 ]. Physical activity level was determined by the validated China Leisure Time Physical Activity Questionnaire (CLTPAQ) [ 27 ], which was a modified version of the Minnesota Leisure Time Physical Activity Questionnaire (MLTPAQ) [ 28 ] adapted to Chinese lifestyle and cultural background. As previously detailed, CLTPAQ measured the total amount of energy (kcal) per week spent on a series of commonly performed physical activities, and the sex-specific threshold for low physical activity was the lowest 20th sex-specific percentile value of total energy consumption [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…McLeroy et al ( 50 ) introduced the social-ecological model into health research, noting that behavior is determined by intrapersonal factors, interpersonal processes, primary groups, institutional factors, community factors, and public policies. The socio-ecological model is often used to analyze the influencing factors of health-related factors, such as eating behaviors ( 51 ), physical activity ( 52 ), and mental wellbeing ( 53 ). The socio-ecological model differs from traditional psychological models in that it explicitly combines direct external influences with peripheral factors, making the socio-ecological model popular in the public health realm ( 54 ).…”
Section: Theoretical Model and Hypothesesmentioning
confidence: 99%